Impulsive Buying Tendency: Elaboration Likelihood Model Perspective - Wibisono, Leonard Junio; Gosal, Gladys Greselda; Teofilus, Teofilus; Effendy, Junko Alessandro; Sabar, Sabar; Azizurrohman, Muhammad (Universitas Brawijaya, Indonesia, 2024)
The increasing percentage of e-commerce users each year, accompanied by the growing convenience of online shopping, is considered to have led to the phenomenon of impulse buying tendency, especially in the context of e-commerce usage. This study aims to discuss the occurrence of impulse buying tendency in Indonesia based on the perspectives of the Elaboration Likelihood Model and Regulatory Focus Theory, using information transparency to represent the central route, celebrity endorsers to represent the peripheral route, and regulatory focus as a moderating variable. The research is focused on Shopee, which is one of the most popular e-commerce in Indonesia, therefore the population is Shopee users in Indonesia. The purposive sampling technique was used with a total of 445 respondents, which were taken from 5 top universities in Indonesia. The results of this study indicate that both information transparency and celebrity endorsers have a significant influence on impulse buying tendencies. Furthermore, regulatory focus is found to be a significant moderating variable of the relationship between information transparency and impulse buying tendency, however, there is no significant effect found on the moderating role of regulatory focus in the relationship between celebrity endorsers and impulse buying tendency. Referring to this, it is hoped that the Shopee e-commerce company can provide information according to the needs of consumers and consider the selection of supporting celebrities in accordance with the products or brands offered.